Factors hindering Indonesian lecturers from publishing articles in reputable international journals - Safnil Arsyad; Bambang Kaswanti Purwo; Katharina Endriati Sukamto; Zifirdaus Adnan (Journal on English as a Foreign Language, 2019)
The purpose of this study is to investigate the possible factors inhibiting the university lecturers or professors in Indonesia from publishing their research results in reputable international journals in English. The research used a mixed (quantitative and qualitative) method, employing a national survey and in-depth interviews with selected lecturers and researchers in five different universities in Indonesia (i.e., Bengkulu University, Padang State University, Makasar State University, Unika Atma Jaya University and Mataram University). The results show that three main factors have hindered the lecturers from submitting their articles to reputable international journals: lack of self-confidence on the quality of their own research and article, finding it very difficult and very time consuming to prepare an article in English and no adequate reward for those who can successfully publish in reputable international journals. However, the majority of them have a positive attitude toward international journal publication for their own benefits or for the sake of their institution.